Sarcopenia in Children With End-Stage Liver Disease. Issue 2 (February 2018) - Lurz, Eberhard; Patel, Hiten; Frimpong, Richard G.; Ricciuto, Amanda; Kehar, Mohit; Wales, Paul W.; Towbin, Alexander J.; Chavhan, Govind B.; Kamath, Binita M.; Ng, Vicky L.
ABSTRACT: Background: Sarcopenia, reflected by decreased psoas muscle surface area (PMSA), has been identified as a novel and independent predictor of wait-list mortality and outcomes in adult liver transplantation (LT). We hypothesized that children with end-stage liver disease (ESLD) would have smaller PMSA than healthy controls. Methods: Computer tomography images of children (ages 0 to 18 years) listed for LT in 2015 and a control group comprised 2:1 age- and gender-matched healthy pediatric trauma victims were reviewed. PMSA was determined at 2 intervertebral disc (L3/4; L4/5) levels. A subset of images was reviewed by 2 radiologists to determine interrater correlation. Results: A total of 23 children with ESLD were included, and the most prevalent diagnosis was biliary atresia (61%). On both lumbar levels, median PMSA was significantly smaller in ESLD subjects compared with the 46 healthy controls (L4/5; median total PMSA (tPMSA) 407 mm 2 (interquartile range 339–537) versus controls 513 mm 2 (interquartile range 437–672); P  = 0.004), independent of participants' weight z scores (r = 0.01; P  = 0.95). Excellent interrater correlation was seen (intraclass correlation 0.99). Conclusions: In this retrospective pilot study, PMSA was significantly lower in children with ESLD compared with healthy age- and gender-matched controls. Because this finding was independent of growth in ESLD subjects, PMSA may represent a novel objective nutritional biomarker in children with advanced liver disease. Abstract : Supplemental Digital Content is available in the text